Antimicrobial Resistance in Bacterial Poultry Pathogens: A Review - Nhung, Nguyen Thi; Chansiripornchai, Niwat; Carrique-Mas, Juan J. (Frontiers in Veterinary Science, 2017)
Antimicrobial resistance (AMR) is a global health threat, and antimicrobial usage and AMR in animal production is one of its contributing sources. Poultry is one of the most widespread types of meat consumed worldwide. Poultry flocks are often raised under intensive conditions using large amounts of antimicrobials to prevent and treat disease, as well as for growth promtoion. AMR in poultry pathogens may result in treatment failure, leading to economic losses, but also be a source of resistance bacteria/genes (including zoonotic bacteria) that may represent a risk to human health. Here we reviewed data on antimicrobial resistance in 12 poultry pathogens (avian pathogenic Escherichia coli, APEC), Salmonella Pullorum/Gallinarum, Pasteurella multocida, Avibacterium paragallinarum, Gallibacterium anatis, Ornitobacterium rhinotracheale (ORT), Bordetella avium, Clostridium perfringens, Mycoplasma spp., Erysipelothrix rhusiopathiae, and Riemerella anatipestifer). A number of studies have demonstrated increases in resistance over time for Salmonella Pullorum/Gallinarum, Mycoplasma gallisepticum, and Gallibacterium anatis. Among Enterobacteriaceae, APEC isolates had median resistance levels over >80%for ampicillin, amoxicillin, tetracycline across studies; these resistance levels were considerably higher compared with S. Pullorum/Gallinarum. Among the Gram-negative, non-Enterobacteriaceae pathogens, ORT had the highest levels of phenotypic resistance with median levels of AMR against cotrimoxazole, enrofloxacin, gentamicin, amoxicillin and ceftiofur all exceeding 50%. In contrast, levels of resistance among P. multocida isolates were less than 20% for all antimicrobials. The study highlights considerable disparities in methodologies, as well as in criteria for phenotypic antimicrobial susceptibility testing and result interpretation. It is necessary to increase efforts to harmonize testing practices, and to promote free access to data on AMR in order to improve treatment guidelines as well as to monitor the evolution of AMR in poultry bacterial pathogens.